Investigating Users’ Perceived Credibility of Real and Fake News Posts in Facebook’s News Feed: UK Case Study - Bates, Neil; Sousa, Sonia C. (My University, 2021)
The purpose of this research was to understand differences in UK users’ perceived credibility of real and fake news posts in Facebook’s news feed based on location, age, gender, education level, frequency of Facebook use, and intention to interact. A survey was designed to collect and measure demographic data from UK-based Facebook users, their behaviors, and perceived credibility of real and fake news posts. The study has made it evident that the perceived credibility of a Facebook post is dependent on the post origin and its truthfulness. The study also points to an interesting phenomenon that users are more likely to interact with posts that are seen as more credible.
Keywords: Brexit; Credibility; Facebook; Fake new; Human factors; News feed; Tabloids; United Kingdom